Analysis of T cell responses to chimpanzee adenovirus vectors encoding HIV gag–pol–nef antigen. Issue 51 (16th December 2015) - Herath, S.; Le Heron, A.; Colloca, S.; Bergin, P.; Patterson, S.; Weber, J.; Tatoud, R.; Dickson, G.
Abstract: Adenoviruses have been shown to be both immunogenic and efficient at presenting HIV proteins but recent trials have suggested that they may play a role in increasing the risk of HIV acquisition. This risk may be associated with the presence of pre-existing immunity to the viral vectors. Chimpanzee adenoviruses (chAd) have low seroprevalence in human populations and so reduce this risk. ChAd3 and chAd63 were used to deliver an HIV gag, pol and nef transgene. ELISpot analysis of T cell responses in mice showed that both chAd vectors were able to induce an immune response to Gag and Pol peptides but that only the chAd3 vector induced responses to Nef peptides. Although the route of injection did not influence the magnitude of immune responses to either chAd vector, the dose of vector did. Taken together these results demonstrate that chimpanzee adenoviruses are suitable vector candidates for the delivery of HIV proteins and could be used for an HIV vaccine and furthermore the chAd3 vector produces a broader response to the HIV transgene.